The “mourning instead”: sensory differences and autistics’ social trauma - Marinoudi, Soula (The Greek Review of Social Research, 2022)
The article explores autistics’ experiences in the context of social relations regulated by cultural representations. The sense of ‘‘mourning’’ which often describes the affective procedure of parents in relation to their children’s diagnosis, as well as their life with them, takes meaning in specific contexts. In opposition to the dominant medical approach to autism, the article focuses on the difference produced when somatic, sensory, perceptual autistic experiences interweave with social expectations. The elaboration of the socially unexpected turbulence between linguistic expression and affective experiences aims at contributing to the discussion on the ways disability and impairment, society and subjectivities are linked with each other. It is suggested that the acceptance of autistics’ difference in a sense of somatic and mental diversity instead of deficit to the norms, presupposes the redefinition of categories of the self, embodiment and culture.